FACTOR THAT INFLUENCE EMPLOYEE PERFORMANCE STUDY CASE : CICENDO DISTRICT OFFICE BANDUNG CITY - Hendrayana, Muhammad Elfriandri; Febriansyah, Hary (Journal of Business and Management, 2017)
Abstract. This research aim to know the factors that influence performance of employee at Cicendo district office Bandung city. The reseacrh has the 3 variable independent there are competences, work culture, & compensation and also 1 variable dependent which is performance. To know  how  influence given by independent variable to dependent variable, this research using multiple linear regression. Multiple linear regression is a model to see that whether there relationship between independent variable and dependent variable. The respondent of this research are all of employees at Cicendo district office Bandung city. The number of respondent is 25 employee. This research spread the questionnaire to all employees of  Cicendo district office Bandung city.. The results of this questionnaire collection are then processed using Statistical Product and Service Solution (SPSS) program. The results obtained are whether the competence, work culture, and compensation influence simultaneous and partial to the performance of employees in the  Cicendo district office Bandung city.Keyword : Compensation, Work Culture, Compensation, Performance, Employee